Predictors of hospital and one-year mortality in intensive care patients with refractory status epilepticus: a populationbased study - Kantanen AM; Kalviainen R; Parviainen I; Ala-Peijari M; Backlund T; Koskenkari J; Laitio R; Reinikainen M (BIOMED CENTRAL LTD, 2022)
Background: The aim was to determine predictors of hospital and 1-year mortality in patients with intensive care unit (ICU)-treated refractory status epilepticus (RSE) in a population-based study.Methods: This was a retrospective study of the Finnish Intensive Care Consortium (FICC) database of adult patients (16 years of age or older) with ICU-treated RSE in Finland during a 3-year period (2010-2012). The database consists of admissions to all 20 Finnish hospitals treating RSE in the ICU. All five university hospitals and 11 out of 15 central hospitals participated in the present study. The total adult referral population in the study hospitals was 3.92 million, representing 91% of the adult population of Finland. Patients whose condition had a post-anoxic aetiological basis were excluded.Results: We identified 395 patients with ICU-treated RSE, corresponding to an annual incidence of 3.4/100,000 (95% confidence interval (CI) 3.04-3.71). Hospital mortality was 7.4% (95% CI 0-16.9%), and 1-year mortality was 25. 4% (95% CI 21.2-29.8%). Mortality at hospital discharge was associated with severity of organ dysfunction. Mortality at 1 year was associated with older age (adjusted odds ratio (aOR) 1.033, 95% CI 1.104-1.051, p = 0.001), sequential organ failure assessment (SOFA) score (aOR 1.156, CI 1.051-1.271, p = 0.003), super-refractory status epilepticus (SRSE) (aOR 2.215, 95% CI 1.20-3.84, p = 0.010) and dependence in activities of daily living (ADL) (aOR 2.553, 95% CI 1.537-4.243, p < 0.0001).Conclusions: Despite low hospital mortality, 25% of ICU-treated RSE patients die within a year. Super-refractoriness, dependence in ADL functions, severity of organ dysfunction at ICU admission and older age predict long-term mortality.